The sense of smell is not strongly affected by ambient temperature and humidity: a prospective study in a controlled environment - Drews, T.; Nehring, M.; Werner, A.; Hummel, T. (European archives of oto-rhino-laryngology, 2021)
Introduction The sense of smell is dependent on environmental conditions. In this study, we analysed the effect of temperature and humidity on the ability to smell. Methods Using the controlled setting of a hypobaric climate chamber 50 healthy participants (40 men, 10 women; mean age of 33 years) completed repeated testing in 4 different settings—cold/dry, cold/humid, warm/dry, warm/humid. The temperatures were 20–35 °C, respectively, and the humidity was set at 30–75%. Testing was performed using the “Sniffin’ Sticks” test battery (odour threshold, discrimination and identification) in a semi-randomised order and in controlled atmospheric pressure conditions. Results The analysis showed that neither temperature nor humidity had a significant effect on olfactory test results. This indicates that olfactory functions in healthy, young subjects with an excellent sense of smell are not strongly affected by temporary changes in environmental conditions.